Pressure‐Dependent Polymorphism and Band‐Gap Tuning of Methylammonium Lead Iodide Perovskite. Issue 22 (21st April 2016) - Jiang, Shaojie; Fang, Yanan; Li, Ruipeng; Xiao, Hai; Crowley, Jason; Wang, Chenyu; White, Timothy J.; Goddard, William A.; Wang, Zhongwu; Baikie, Tom; Fang, Jiye
Abstract: We report the pressure‐induced crystallographic transitions and optical behavior of MAPbI3 (MA=methylammonium) using in situ synchrotron X‐ray diffraction and laser‐excited photoluminescence spectroscopy, supported by density functional theory (DFT) calculations using the hybrid functional B3PW91 with spin‐orbit coupling. The tetragonal polymorph determined at ambient pressure transforms to a ReO3 ‐type cubic phase at 0.3 GPa. Upon continuous compression to 2.7 GPa this cubic polymorph converts into a putative orthorhombic structure. Beyond 4.7 GPa it separates into crystalline and amorphous fractions. During decompression, this phase‐mixed material undergoes distinct restoration pathways depending on the peak pressure. In situ pressure photoluminescence investigation suggests a reduction in band gap with increasing pressure up to ≈0.3 GPa and then an increase in band gap up to a pressure of 2.7 GPa, in excellent agreement with our DFT calculation prediction. Abstract : Band aid : Through the determination of methylammonium lead iodide perovskite crystallographic transitions under pressure, in situ laser‐excited photoluminescence suggests a reduction in band gap in the tetragonal phase on increasing the pressure up to about 0.3 GPa and then an increase in band gap in ReO3 ‐type cubic phase up to a pressure of 2.7 GPa, a result that is supported by DFT calculations.